2022
DOI: 10.3390/nu14245300
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Decline Related to Diet Pattern and Nutritional Adequacy in Alzheimer’s Disease Using Surface-Based Morphometry

Abstract: Dietary pattern (DP) results in nutrition adequacy and may influence cognitive decline and cortical atrophy in Alzheimer’s disease (AD). The study explored DP in 248 patients with AD. Two neurobehavioral assessments (intervals 13.4 months) and two cortical thickness measurements derived from magnetic resonance images (intervals 26.5 months) were collected as outcome measures. Reduced rank regression was used to assess the groups of DPs and a linear mixed-effect model to explore the cortical neurodegenerative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…It is noteworthy that coffee/tea consumption emerged as a common influencing factor in the dietary patterns of both genders. The intake of coffee/tea proved beneficial for cognition, directly impacting cognitive outcomes, consistent with other reports [ 20 , 29 , 30 ]. We believe that caffeine intake from coffee and tea affects MMSE cognitive performance, although there are conflicting findings in the literature [ 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is noteworthy that coffee/tea consumption emerged as a common influencing factor in the dietary patterns of both genders. The intake of coffee/tea proved beneficial for cognition, directly impacting cognitive outcomes, consistent with other reports [ 20 , 29 , 30 ]. We believe that caffeine intake from coffee and tea affects MMSE cognitive performance, although there are conflicting findings in the literature [ 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…The food frequency questionnaire (FFQ) contains 22 food groups, and it was conducted by trained interviewers to assess dietary intake in the AD patients. To avoid possible recall bias, the FFQ was recorded by the major caregiver of the patients [20]. The frequency of intake was coded as follows: (1) Never eat or eat less than once a month, (2) Eat 1-3 times a month, (3) Eat 1-2 times a week, (4) Eat 3-4 times a week, (5) Eat 5-6 times a week, (6) Eat 1-2 times a day, (7) Eat more than 3 times a day.…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…Specific foods and dietary habits can affect the structure and abundance of different strains of microbiota in the intestine, which is implicated in the maintenance of human homeostasis, more generally. As an example, a recent study has reported that AD patients with better global cognition had more ingestion of coffee or tea [ 8 ]. Furthermore, the Mediterranean diet pattern and high intake of plant-based foods, especially those rich in polyphenols might delay an AD diagnosis and increase the levels of fecal short chain fatty acids and bile acids [ 7 ].…”
mentioning
confidence: 99%